1998
DOI: 10.1016/s0737-6782(97)00068-4
|View full text |Cite
|
Sign up to set email alerts
|

When product development performance makes a difference: A statistical analysis in the electronics industry

Abstract: Throughout the pages of JPIM and other publications, researchers and practitioners devote considerable effort to identifying the dimensions of new-product development (NPD) performance that relate most closely to business success. Although we may hope to unveil a set of universal truths about the relationship between NPD performance and business success, the relevant NPD performance measures appear to depend on the industry in which a firm competes.In fact, Christian Terwiesch, Christoph Loch, and Martin Niede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 33 publications
(26 reference statements)
2
19
0
Order By: Relevance
“…For example, Griffin (1997) reports that bestpractice firms realize 49 percent of their sales from products developed and launched in the last five years and that new product performance accounts for onefourth of the variability in organizational performance. Similarly, Terwiesh et al (1998) report that new product performance explains, depending upon the market context, between 30 and 70 percent of organizational profitability variance. Accordingly, it is hypothesized that H8: The better the new product performance, the better the organizational performance.…”
Section: The Relationship Between New Product Performance and Organizmentioning
confidence: 99%
“…For example, Griffin (1997) reports that bestpractice firms realize 49 percent of their sales from products developed and launched in the last five years and that new product performance accounts for onefourth of the variability in organizational performance. Similarly, Terwiesh et al (1998) report that new product performance explains, depending upon the market context, between 30 and 70 percent of organizational profitability variance. Accordingly, it is hypothesized that H8: The better the new product performance, the better the organizational performance.…”
Section: The Relationship Between New Product Performance and Organizmentioning
confidence: 99%
“…In addition to product development, the overall instrument contained questions on marketing, manufacturing, finance and top management, which were used in other research projects (e.g. Terwiesch et al 1998). The product development part consisted of a group of general questions concerning product development practices of the business unit, and a subsection for each of two specific projects.…”
Section: Data Collectionmentioning
confidence: 99%
“…Griffin (1997) also reported that new products launched in firms in the last 5 years contributed to 49% of their revenue, and that new product performance has increased dramatically from 30% to 70% of firms' profitability variance, based on the market context (Terwiesh et al, 1998). Therefore, we propose the following hypothesis:…”
Section: New Product Performance and Marketing Performance Of Contracmentioning
confidence: 91%